Characterization of Microsatellite Primers in the Endangered Orchid Phaius australis and Cross‐Amplification to P. bernaysii (Orchidaceae). (22nd December 2017) - Simmons, Catherine L.; Lamont, Robert W.; Shapcott, Alison
Abstract : Premise of the study: The swamp orchid, Phaius australis (Orchidaceae), is nationally endangered due to illegal collection and habitat loss and fragmentation, resulting in a disjunct distribution in spring and coastal wetland ecotones along Australia's east coast. Polymorphic microsatellite markers were developed to study genetic diversity and population structure for conservation and restoration purposes. Methods and Results: Illumina HiSeq high‐throughput sequencing was used to develop 15 nuclear microsatellite markers, including 10 polymorphic markers for P. australis. Polymorphism at each marker was evaluated using 90 individuals from four natural populations. The number of alleles per locus ranged from one to three, and the observed and expected heterozygosity varied from 0.036 to 0.944 and from 0.035 to 0.611, respectively. These markers transferred successfully to congener P. bernaysii. Conclusions: The microsatellite markers will be useful for revealing levels of genetic diversity and gene flow for P. australis and may inform future conservation efforts.